EVALUASI DAN REKOMENDASI PENINGKATAN PADA WEBSITE DINAS PERPUSTAKAAN DAN KEARSIPAN SLEMAN - Putra, Prananda; Dirgahayu, Teduh (STKIP PGRI Situbondo, 2025)
This study evaluates the user interface (UI) design and user experience (UX) of the website for the Dinas Perpustakaan dan Kearsipan Sleman in Indonesia. Digital transformation has made the library's website an essential resource for public information. However, issues related to UI and UX design often hinder the user experience, causing difficulties in finding information and interacting with online features. This research aims to conduct an in-depth analysis of the website and provide recommendations for innovative improvements. The methods used include the creation of user personas, user stories, and user journeys, followed by testing with selected participants through observation, interviews, and the System Usability Scale (SUS). Findings reveal deficiencies in the interface design that impact efficiency and accessibility. Test results indicate that participants had difficulty finding the information they needed, and interviews revealed obstacles in executing the tasks given. Recommendations for improvements include simplifying navigation, enhancing visual aesthetics, and refining the interface to improve user satisfaction and experience.